An exploratory study of mental health among Muslim creative media workers - Baharudin, Dini Farhana; Sumari, Melati; Mohamad Yusop, Yusni; Zainudin, Zaida Nor (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: The advancement of technology and an ecological shift in the creative media industry requires managers and TV production workers to adapt to changes to ensure their well-being. Recent development shows a growing concern for the mental, physical and social health of creative media workers that demands a more in-depth investigation. Studies have found that those working in television production are facing long hours of work, poor pay, isolation and insecurity. However, there is little empirical research undertaken on those who work in the Malaysian creative media industry, especially Malay Muslims. Studies of media workers in Malaysia are mostly concerned with news production and the impact of reporting and journalistic challenges. The purpose of this study is to explore how Malay Muslim creative media workers manage and negotiate their mental health and well-being issues. Methods: By employing a phenomenological approach, interviews were conducted with seven participants, exploring their experience in the creative media industry. Results: The study found four emergent themes: (a) passion and commitment for creative endeavours, (b) work culture, (c) issue on work-life balance, and (d) role of religion. Discussion: This study is an attempt towards understanding the mental health of those working in the creative and entertainment realms in Malaysia. Based on the findings, implication for practitioners and future studies are discussed.